Half a century of environmental variability and seabird trends on the Faroe Shelf in the North Atlantic Ocean - Olsen, Bergur; Anker-Nilssen, Tycho; Danielsen, Jóhannis; Gaard, Eilif; Hansen, Leivur Janus; Jacobsen, Sólvá; Jensen, Jens-Kjeld; Olsen, Regin; Salter, Ian; Hátún, Hjálmar (Frontiers in Marine Science, 2025)
The Faroe Shelf, located on the North Atlantic’s Iceland-Scotland ridge, has historically hosted a rich ecosystem with large seabird populations. However, substantial declines in their population sizes have been observed over the past half century. This study introduces and documents comprehensive decades-long data series from 1972-present on offspring production and adult attendance of four seabird species, the common guillemot, Atlantic puffin, black-legged kittiwake, and Arctic tern, breeding in major colonies in the Faroe Islands. Results show that the highly variable productivity of these seabirds is characterized by marked and synchronized peaks at 5- to 10-years intervals, and these peaks closely mirror indices of primary production and availability of pelagic juvenile fish on the Faroe shelf. These ecological signals are examined in the context of oceanographic changes in the subpolar North Atlantic Ocean, and we argue that the presented seabird series can serve as indicators to enhance the understanding of the Faroe shelf ecosystem and inform the management of both seabird populations and commercial fish stocks.